New barley variety "Ay" released by National Agricultural Research Systems (NARS) in Turkey - CGIAR Research Program on Livestock (2020)
ICARDA holds the global mandate within the CGIAR system to breed barley. The ICARDA Barley International Nurseries (IN) have to date released more than 250 barley varieties of ICARDA origin and made them available to partners. The "Ay" variety has been released and is available to farmers in Turkey.